Factors Influencing Young Consumers’ Purchasing Decisions on TikTok Shop in Vietnam: The Role of Advertising Attributes - Thuy Nguyen Thi Thu; Ha Dinh Thi (Transpublika Publisher, 2026)
In the context of Vietnam’s rapid digital transformation, TikTok Shop has emerged as a leading social commerce platform, especially for young people. This research aims to analyze the factors influencing consumers’ purchasing decisions on the TikTok Shop platform through advertising activities. The research uses a quantitative research method, surveying 178 respondents, mainly University students in Vietnam. Data analysis methods included Cronbach’s Alpha coefficient testing, exploratory factor analysis (EFA), and linear regression using SPSS software. Based on the synthesis and analysis of aspects of digital advertising, the research initially proposed seven factors. However, the regression analysis confirmed that only three key factors significantly influence purchasing decisions: trust, interactivity, and brand awareness. Factors such as entertainment, information quality, annoyance, and incentive factors did not reach statistical significance or correlation in the final model. The results indicate that enhancing trust, increasing interactivity, and building brand awareness will be the core factors boosting consumers’ purchase intentions and behaviors on TikTok Shop. These findings not only add to the theoretical framework of digital consumption but also provide practical implications for businesses to optimize their marketing strategies on TikTok by prioritizing building credibility, brand recognition, and enhancing two-way interaction rather than overusing intrusive advertisements.